Citra Perusahaan, Kualitas Produk dan Harga terhadap Kepuasan Pelanggan - Suriani, Suriani; Putra, Pandi; Alimuddin, Firman; Rifani, Riza Amalia (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This study aims to determine the effect of corporate image, product quality and price on customer satisfaction at PT. Manuntung Raya Sidrap using the SPSS 23 analysis method. The type of research used is descriptive research and data collection techniques through questionnaires, while the sample treatment method is to determine the roscoe formula as many as 60 the number of respondents. The analytical method used is multiple linear regression analysis method.The results showed that: 1. Corporate image (X1) test results showed a value of tcount (1.587) < ttable (2.003) with a significant value (0.120) > (0.05). 2. Product Quality (X2) test results show t count (-2.064) > t table (2.003) with a significance value (0.045) < (0.05). 3. Price (X3) test results show t count (7.513) > t table (2.003) with a significance value (0.000) < (0.05). Fcount = (21.580) > Ftable (0.277) with a significance value of (0.000) < (0.05) which means that Corporate Image, Product Quality and Price simultaneously influence customer satisfaction. The coefficient of determination R square is 0.612 points or 61.2% which means that the variables of company image, product quality and price can be explained equally as increasing 61.2% of PT. Manuntung Raya Sidrap, while the remaining 38.8% is influenced by other factors that are not the focus of this research object.